Environmental Management Accounting Assistance at TPST 3R Mulyoagung Bersatu - Putra, Indra Lukmana; Junus, Mochammad; Imam, Muhammad Kholisul; Rachmah, Siti; Risdiana, Devi Mega; Khoiriyah, Rizqiyatul (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The Community Engagement Program (PKM) aims to address the challenges faced by TPST 3R Mulyoagung Bersatu in managing financial data related to waste management. Enhance their capacity in Environmental Management Accounting through targeted mentoring and accountability. Method: Activities were conducted under an existing MoU between Politeknik Negeri Malang and TPST 3R Mulyoagung Bersatu. A participatory, hands-on approach was used, involving field observations, informal discussions, and interactive training sessions tailored to the partner’s specific needs..  Practical Applications: Participants gained practical knowledge in applying environmental accounting principles in their daily operations. The training improved their ability to systematically record and manage financial data, directly contributing to more transparent and efficient 3R waste management practices. Conclusion: The program successfully strengthened the understanding and implementation of environmental accounting among TPST managers. It exemplifies productive collaboration academia and the community, where mutual learning leads to sustainable and impactful solutions for environmental challenges.